Postoperative Cognitive Dysfunction: A Narrative Literature Review - Awang Budi Saksono (Open Access Indonesian Journal of Medical Reviews, 2021)
Postoperative cognitive impairment includes memory problems, difficulty concentrating, problems solving problems, and decreased thinking skills. This literature review aimed to describe postoperative cognitive dysfunction in clinical practice. In general, the occurrence of POCD is associated with inflammation and physiological changes in the brain that affect cognitive function. The mechanism by which postoperative cognitive dysfunction (POCD) occurs is not fully understood. However, several factors, such as inflammatory reactions, drug influence, anesthesia, and other factors, are thought to play a role in the occurrence of this condition. Postoperative cognitive dysfunction (POCD) and postoperative delirium (POD) are two conditions that are closely related and often interrelated. POD can trigger a systemic inflammatory reaction which then triggers POCD, and people who experience POD tend to be more likely to develop POCD. In conclusion, POCD can be seen in most postoperative patients in the old patient. With the high number of geriatric patients doing surgery, the effect of anesthesia and surgery on the risk of dementia is high. Geriatric mental status needs to be monitored before and after surgery because the old patient can quickly experience cognitive dysfunction after surgery.